Peningkatan Aktivitas dan Prestasi Belajar Matematika Materi Pengolahan Data Menggunakan Metode Kerja Kelompok pada Siswa Kelas VI SDN 3 Sribhawono Lampung Timur TP 2017/2018 - Suwarti Suwarti (Pedagogia: Jurnal Ilmiah Pendidikan Dasar Indonesia, 2021)
The purpose of this study is to describe the increase in learning activity and achievement using the group work method, in class VI mathematics learning at SDN 3 Sribhawono East Lampung TP 2017/2018. The method used is Classroom Action Research (CAR). Data collection techniques with observation guidelines to obtain data about student learning activities and learning achievement tests at the end of each research cycle. Furthermore, the data obtained were analyzed descriptively qualitatively. The results showed that the use of the group work method can increase the activity and achievement of learning mathematics in class VI SDN 3 Sribhawono Lampung.